Елліністичні глиняні півфігури з Ольвії - Шевченко, Т.М. (Археологія і давня історія України, 2016)
Публікуються півфігурні теракотові зображення жіночих персонажів з колекції розкопок
Л.М. Славіна, які зберігаються в НФ ІА НАН України, аналізується їх атрибуція, причини поширення
в елліністичний період і способи використання в культовій практиці. В статье публикуются полуфигурные терракотовые изображения женских персонажей эллинистического периода из коллекции Л.М. Славина, хранящейся в Научных фондах Института археологии
НАНУ. Дается краткое описание, место находки и датировка. Published here are half-figured terracotta female
depictions of the Hellenistic period from the collection
of excavations by L.M. Slavin kept in the Scientific
Funds of the Institute of Archaeology, NAS of Ukraine.
Brief descriptions, the places of find, and the dates are
presented. Discussed both known in the literature depiction
of a goddess in chiton, and similar fragments,
as well as two analogous depictions of a goddess with
a wreath, which owing to its recently found fragments
unpublished before, should be also referred to half-figures.
Taking into account the new research, the attribution
is specified. Not all the half of the figure depictions represent Kore-Persephone. Various handmade
details on headdresses and decorations, attached after
moulding in cast, correspond to the images of many goddesses related to the family cults, including the images
of Dionysus cult participants. The impetus for creating only half of a figure was
more of an issue of function and convenience in usage. During the Hellenistic period, locally made terracottas
increase in size and loose in elegance, and at the same time the attention is paid to the face and decorations.
More heavy and bulky statuettes required unprecedented skills from the coroplast to make them steady
and convenient in their usage as votives. Half-figures were the solution of this task. With larger faces and
decorations, and at the same time, not too big to be unsteady, with the wide lower part and thick smoothly
cut edge, they were easily placed on the offering table or other horizontal surface.